Determining Ultralow Absorption Coefficients of Organic Semiconductors from the Sub‐Bandgap Photovoltaic External Quantum Efficiency. Issue 1 (22nd November 2019) - Kaiser, Christina; Zeiske, Stefan; Meredith, Paul; Armin, Ardalan
Abstract: Energy states below the bandgap of a semiconductor, such as trap states or charge transfer states in organic donor–acceptor blends, can contribute to light absorption. Due to their low number density or ultrasmall absorption cross‐section, the absorption coefficient of these states is challenging to measure using conventional transmission/reflection spectrophotometry. As an alternative, the external quantum efficiency (EQE) of photovoltaic devices is often used as a representative of the absorption coefficient, where the spectral line shape of the EQE is considered to follow the absorption coefficient of the active layer material. Here, it is shown that the sub‐bandgap EQE is subject to thickness dependent low finesse cavity interference effects within the device—making this assumption questionable. A better estimate for the absorption coefficient is obtained when EQE spectra corresponding to different active layer thicknesses are fitted simultaneously for one attenuation coefficient using an iterative transfer matrix method. The principle is demonstrated for two model acceptor–donor systems (PCE12‐ITIC and PBTTT‐PC71 BM) and accurate subgap absorption coefficients are determined. This approach has particular relevance for both understanding subgap states and their utilization in organic optoelectronic devices. Abstract : The absorption coefficient in the weakly absorptive region of the spectrum is of great importance for thin‐film solar cells and photodiodes. This study presents a method for obtaining the sub‐bandgap absorption coefficient from multiple external quantum efficiency (EQE) spectra.